2015
DOI: 10.1111/andr.12055
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic androgen receptor deficiency promotes visceral fat deposition in male mice without impairing glucose homeostasis

Abstract: SUMMARY Androgen deficiency in men increases body fat, but the mechanisms by which testosterone suppresses fat deposition have not been elucidated fully. Adipose tissue macrophages express the androgen receptor (AR) and regulate adipose tissue remodeling. Thus, testosterone signaling in macrophages could alter the paracrine function of these cells and thereby contribute to the metabolic effects of androgens in men. A metabolic phenotyping study was performed to determine whether the loss of AR signaling in hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 51 publications
(50 reference statements)
2
19
0
Order By: Relevance
“…In addition, this VAT accumulation process can be reversed by testosterone treatment, showing that testosterone replacement might be involved in the treatment strategy for abating VAT deposition caused by testosterone deficiency under HFC diet. These results are consistent with data observed from testosterone deficiency or androgen receptor knockout (ARKO) mice, which showed that castration induced abdominal obesity of HFD mice and this phenomenon could be eliminated by treating with antibiotics [20] and androgen deficiency under HFD significantly enhanced visceral and total fat accumulation of ARKO mice [21]. However, another study discovered there was no significant difference of VAT mass between obesogenic diet-fed (OGD, including greater amounts of sugars, saturated and monounsaturated fat and less protein and polyunsaturated fat compared to the standard rat chow diet) and orchiectomised (OGD + ORX) male mice [22].…”
Section: Discussionsupporting
confidence: 89%
“…In addition, this VAT accumulation process can be reversed by testosterone treatment, showing that testosterone replacement might be involved in the treatment strategy for abating VAT deposition caused by testosterone deficiency under HFC diet. These results are consistent with data observed from testosterone deficiency or androgen receptor knockout (ARKO) mice, which showed that castration induced abdominal obesity of HFD mice and this phenomenon could be eliminated by treating with antibiotics [20] and androgen deficiency under HFD significantly enhanced visceral and total fat accumulation of ARKO mice [21]. However, another study discovered there was no significant difference of VAT mass between obesogenic diet-fed (OGD, including greater amounts of sugars, saturated and monounsaturated fat and less protein and polyunsaturated fat compared to the standard rat chow diet) and orchiectomised (OGD + ORX) male mice [22].…”
Section: Discussionsupporting
confidence: 89%
“…Testosterone administration in female to male transsexuals alters adipose tissue distribution, with long-term administration instigating increased visceral fat and decreased subcutaneous fat deposits (6). Additionally, ATMs have been found to express the androgen receptor, potentially contributing to the metabolic effects of androgens in males (43).…”
Section: Discussionmentioning
confidence: 99%
“…Castration studies have been conflicted showing decreased weight [35], improved glucose tolerance [36], increased insulin sensitivity [37], and improved triglycerides [38] even with increased fat mass, with other studies showing that castration impairs glucose tolerance and insulin resistance [39•]. AR-KO mice also show increased adiposity [40] and improved insulin sensitivity consistent with a deleterious role for androgens in adipose tissue [41]. Consistent with this, testosterone replacement in castrated mice decreases energy expenditure, decreases adiposity, elevates triglyceride levels, and impairs metabolism.…”
Section: Animal Models Identify Sex Differences In Adipose Tissue Biomentioning
confidence: 99%